Assessment of mixed mode crack propagation of crane runway girders subjected to cyclic loading. (March 2016) - Rettenmeier, Philipp; Roos, Eberhard; Weihe, Stefan; Schuler, Xaver
Highlights: An assessment of crack propagation of crane runway girders is proposed. The crane runway girders were travelled over by wheel loads in fatigue tests. Shear mode growth was determined by means of fractographic investigations. The cyclic wheel load causes non-proportional mixed mode crack tip loading. Numerically predicted total numbers of cycles accord to experimental results. Abstract: Crane runway girders are subjected to travelling wheel loads resulting in mixed mode crack tip loading. The paper addresses the assessment of crack propagation of crane runway girders being travelled over by wheel loads. Fractographic investigations of crack surfaces show shear mode crack growth and scabs due to friction between the crack flanks. Crack growth rates for steels subjected to tensile mode crack growth are evaluated. Stress intensity factors of crane runway girders under cyclic loading are obtained by numerical investigations. Numbers of cycles of crack growth are calculated by use of the shear stress intensity factor K τ .